Transporte de partículas em sistemas mesoscópicos - Silva, Petrúcio Barrozo da (2009)
In this work we investigate the transport properties of particles in mesoscopic systems. In the first part, we use the model originally proposed by Zapperi et al. (Phys. Rev. Lett. 86, 3622 (2001)) to describe the steady-state transport of overdamped particles in the presence of an obstacle and confined to a channel with width of the order of the characteristic size of the system. With this model, we obtain a non-linear first-order differential equation, whose solution in 1D is capable to describe the behavior of the particle density along a 2D channel for different particle systems (e.g., superconducting vortices, colloids and pedestrians, all simulated with molecular dynamics) and obstacle types (e.g, one energy barrier, a channel constriction and a network of pinning centers). We observe that such a model can be used to represent the flow of any system of overdamped particles, as long as the interactions between them can reach a distance greater than only the first neighbors. In the second part of this work, we investigate the flow of interacting particles (not necessarily overdamped) confined to a channel of asymmetrical walls. Here the main objective is to describe through molecular dynamics techniques both the flow of pedestrians as well as the transport of superconducting vortices through irregular channels. In both cases, we observe that the asymmetry of the confining walls can induce a preferential direction to the flow. In the case of pedestrians, our results indicate that, when two groups of people move in opposite directions in a ratcheted type of corridor, this induced order is also responsible for flow maximization. This order can be destroyed, however, when we change the total number of particles in the system, their target speed, the amplitude of the external added noise or the degree of the asymmetry of the channel. We also observe that the order-disorder transitions in this system are usually followed by metastability and hysteresis cycles. In the case of superconducting vortices, multiple depinning transitions are observed when there is a small comensurability field between the number of ratchets in the channel and the number of particles (vortices) in the system.